Attempted synthesis of a meta-metalated calix[4]arene - Jurisch, Christopher D.; Arnott, Gareth E. (Beilstein Journal of Organic Chemistry, 2019)
An evidence for the formation of a rare meta-metalated inherently chiral calix[4]arene is described. Our strategy involved using a mesoionic carbene to direct C–H activation, but proved to form an unexpectedly unstable intermediate that was identified through high-resolution mass spectrometry. On route to our target, a new optimized method to mononitrocalix[4]arenes was developed, including optimized and high yielding transformations to azide and 1,2,3-triazole derivatives which may have application in other areas of research.
Keywords: calixarene; inherent chirality; mesoionic carbene; mononitration; ruthenacycle

Calixarenes: an introduction - Gutsche, C. (RSC Publishing, 2008)

(untitled) - Wieser, C.; Dieleman, C. B.; Matt, D. (Coord. Chem. Rev., 1997)

(untitled) - Homden, D. M.; Redshaw, C. (Chem. Rev., 2008)

Calixarenes and Beyond - Patil, R. S.; Banerjee, D.; Atwood, J. L.; Thallapally, P. K. (Springer International Publishing, 2016)

(untitled) - Patra, S.; Maity, D.; Gunupuru, R.; Agnihotri, P.; Paul, P. (J. Chem. Sci., 2012)

(untitled) - Song, M.; Sun, Z.; Han, C.; Tian, D.; Li, H.; Kim, J. S. (Chem. – Asian J., 2014)

(untitled) - Schühle, D. T.; Peters, J. A.; Schatz, J. (Coord. Chem. Rev., 2011)

(untitled) - Rebilly, J.-N.; Colasson, B.; Bistri, O.; Over, D.; Reinaud, O. (Chem. Soc. Rev., 2015)

(untitled) - Arnott, G. E. (Chem. – Eur. J., 2018)

Meta Substitution of Calixarenes - Kundrat, O.; Lhoták, P. (Springer International Publishing, 2016)

(untitled) - Xu, Z.-X.; Zhang, C.; Zheng, Q.-Y.; Chen, C.-F.; Huang, Z.-T. (Org. Lett., 2007)

(untitled) - Herbert, S. A.; van Laeren, L. J.; Castell, D. C.; Arnott, G. E. (Beilstein J. Org. Chem., 2014)

(untitled) - Castell, D. C.; Lesotho, N.; Nikolayenko, V. I.; Arnott, G. E. (Eur. J. Org. Chem., 2017)

(untitled) - Holub, J.; Eigner, V.; Vrzal, L.; Dvořáková, H.; Lhoták, P. (Chem. Commun., 2013)

(untitled) - Elaieb, F.; Sémeril, D.; Matt, D.; Pfeffer, M.; Bouit, P.-A.; Hissler, M.; Gourlaouen, C.; Harrowfield, J. (Dalton Trans., 2017)

(untitled) - Slavik, P.; Dudic, M.; Flidrova, K.; Sykora, J.; Cisarova, I.; Böhm, S.; Lhotak, P. (Org. Lett., 2012)

(untitled) - Gaeta, C.; Talotta, C.; Neri, P. (J. Inclusion Phenom. Macrocyclic Chem., 2014)

(untitled) - Poulain, A.; Canseco-Gonzalez, D.; Hynes-Roche, R.; Müller-Bunz, H.; Schuster, O.; Stoeckli-Evans, H.; Neels, A.; Albrecht, M. (Organometallics, 2011)

(untitled) - Donnelly, K. F.; Lalrempuia, R.; Müller-Bunz, H.; Albrecht, M. (Organometallics, 2012)

(untitled) - Canseco-Gonzalez, D.; Albrecht, M. (Dalton Trans., 2013)

(untitled) - Donnelly, K. F.; Lalrempuia, R.; Müller-Bunz, H.; Clot, E.; Albrecht, M. (Organometallics, 2015)

(untitled) - Vivancos, Á.; Segarra, C.; Albrecht, M. (Chem. Rev., 2018)

(untitled) - Gutsche, C. D.; Iqbal, M. (Org. Synth., 1990)

(untitled) - Gutsche, C. D.; Levine, J. A.; Sujeeth, P. K. (J. Org. Chem., 1985)

(untitled) - Dondoni, A.; Marra, A.; Scherrmann, M.-C.; Casnati, A.; Sansone, F.; Ungaro, R. (Chem. – Eur. J., 1997)

(untitled) - Ikeda, A.; Yoshimura, M.; Lhoták, P.; Shinkai, S. (J. Chem. Soc., Perkin Trans. 1, 1996)

(untitled) - Malytskyi, V.; Troian-Gautier, L.; Mattiuzzi, A.; Lambotte, S.; Cornelio, B.; Lagrost, C.; Jabin, I. (Eur. J. Org. Chem., 2018)

(untitled) - Kelderman, E.; Verboom, W.; Engbersen, J. F. J.; Reinhoudt, D. N.; Heesink, G. J. T.; van Hulst, N. F.; Derhaeg, L.; Persoons, A. (Angew. Chem., Int. Ed. Engl., 1992)

(untitled) - Curiel, D.; Beer, P. D. (Chem. Commun., 2005)

(untitled) - Stastny, V.; Lhoták, P.; Michlová, V.; Stibor, I.; Sykora, J. (Tetrahedron, 2002)

(untitled) - Stejskal, F.; Eigner, V.; Dvořáková, H.; Cuřínová, P.; Lhoták, P. (Tetrahedron Lett., 2015)

(untitled) - Byrne, S.; Mullen, K. M. (RSC Adv., 2016)